Ulasan artikel: Elemen dalam Buku Indie: Satu Kajian Grounded Theory Terhadap Mahasiswa Universiti Pendidikan Sultan Idris - Williamson, Kristopher (Penerbit Universiti Kebangsaan Malaysia, 2020)
Independent book publishing in Malaysia has presented typically younger readers with a popular platform for connecting with familiar realities and lived social situations. At the same time, there is resistance to the success of these “indie books” on political, economic, and social fronts by groups that are entrenched in the normative order. At the titular level, Muhammad Atiullah Othman, Nadarajan Thambu, and Siti Noranizahhafizah Boyman’s study, “Elemen dalam Buku Indie: Satu Kajian Grounded Theory Terhadap Mahasiswa Universiti Pendidikan Sultan Idris,” appears to offer a case study on the perceptions of university students toward the various elements found within some indie books. Upon closer examination, however, their study largely ignores student responses and criticizes the entire industry for the perceived and projected negative impact it will have on the nation. The disconnect between the data and their claims is compounded by the authors’ unsupported and highly subjective moral judgments, despite multiple instances of their own unethical academic writing practices.